(untitled) (Eurasian Journal of Ecology, 2016)
The analysis of the number of basic physiological groups of microorganisms conducted in the model experiment showed that introduction of the oily soil zeolite, biovermikompost and biopreparation «Bakoil -KZ» favorably influences on the microflora. Meanwhile, the number of microorganisms increases hydrocarbon by three to four orders. Joint application of these meliorantov clears the soil from oil by 68,5 %, while the activated soil enzymes such as catalase and dehydrogenase .